OdontoTech teaching project: fostering teaching and technological innovation - Experience report of a teaching project (Research, Society and Development, 2021)
The OdontoTech teaching project aimed to address technological innovation and entrepreneurship in the dentistry course, given the deficiency in the Law of Guidelines and Bases for National Education in the academic sphere. This project sought to train students and qualify them to act in the context of the knowledge economy, as an articulating agent and executor of actions aimed at preparing university students for the labor market, in addition to contributing to the promotion of business activity and training from the academic community to entrepreneurship and innovation. In addition, technological education occurs when universities commit to the development of multiple student skills, creating an environment that encourages innovation processes.  The project consisted of twelve fortnightly meetings, with presentation of mini-courses on entrepreneurship and technological innovation, lasting approximately one hour and thirty minutes, held at the Faculty of Dentistry of UFPel. The topics covered followed four thematic axes, namely: “Entrepreneurial experiences”, “Technological innovation”, “Business model planning” and “Information and updating in entrepreneurship”. The project's actions included advice and mentoring on entrepreneurship and technological innovation, in addition to holding biweekly mini-courses on the subject. The fortnightly meetings sought to elucidate in a didactic way the main items that must be observed in a business, in addition to proposing a practical methodology for students through the Canvas tool for strategic planning. This project included approximately two hundred students as listeners. Thus, this experience report sought to describe the actions carried out by the project and their impacts on the academic environment.